Konsep Kepemimpinan Negara Islam (Studi Komparasi Pemikiran al-Mawardi dan Ibnu Taimiyah) - Kasman Bakry; Abdul Haris Abbas; Ashar; Abdullah Nazhim Hamid (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2021)
The objectives of this study is to explore and compare the concept of leadership in an Islamic state according to Ibn Taimiyah and al-Mawardi. This study is a qualitative descriptive comparative study, with normative, conceptual, and historical approach. The result os study reveals that Ibn Taymiyyah pays more attention to the ultimate goal of a state leadership, namely the benefit of the world and the hereafter, while al-Mawardi is more concerned with the government system in the form of imÄmah or khilÄfah.